Representations of the event in the drawings of the civilizations of the ancient world (selected models) (Al-Academy, 2023)
This research is concerned with studying the representations of the event in the drawings of the ancient civilizations of the world, and the research consists of two axes, the axis of the theoretical framework, which included (the research problem, its aim, its limits, and the definition of its terminology). The research aims to reveal how the event pattern was formulated by the artist on the surface of his visual achievement, and the limits of the search were spatial in the ancient civilizations of Iraq, Egypt, Greece and Rome, but the limits of the temporal research could not be determined because they were before birth, and objectively:representations of the event in the civilizations of the ancient world This axis also included four topics The first: the event in the arts of ancient Iraq, the second: the event in the arts of ancient Egypt, the third: the event in Greek art, and the fourth: the event in Roman art, ending with the indicators produced by the theoretical framework, while the second applied axis was represented by the research procedures, namely (the research community The research concluded with the results and the most important sources that the researcher relied on.